Factors Affecting Firm Growth Of Non-Cyclical Consumer Industry Companies Listed on Indonesia Stock Exchange in 2022 - Angsari Sitorani Raharjo; Henny Setyo Lestari (Peneliti.net, 2022)
The primary purpose of this paper is to determine the factors that influence the growth of companies in the non-cyclical consumer industry sector. This sector is an industrial sector that produces or distributes primary consumer goods which are basic needs so that they are not affected by economic growth. The sample consists of 39 companies in the field of consumer non-cyclical listed on the Indonesia Stock Exchange in 2022. This study uses multiple regression analysis to analyze the variables that are the focus of the study. This study showed that company size and return on assets (ROA) significantly positively affected company growth. In contrast, the current ratio had an insignificant negative effect, and company leverage had a positive but not significant effect on company growth. The impact given between variables is statistically significant. Company managers can use this research to optimize company growth. They can pay attention to aspects such as increasing market share, reducing operating costs, increasing profits to increase the company's net income and need to anticipate the impact of competing companies that will affect company revenues